Inovasi Metoda Pekerjaan Jembatan Rangka Baja Studi Kasus: Pembangunan Jembatan Ujung Tanah Ii, Kota Padang, November 1993 - Istijono, Bambang; Narny, Yenny; Hellyward, James; Putra, Rinaldi Eka (Jurnal Talenta Sipil, 2024)
The bridge is one of the most important means of transportation for humans. The bridge also serves as a link between one area and another. Seeing the importance of the function of a bridge, the construction of a bridge must meet various existing standards. One of the requirements that must be met in making a bridge is the resilience of the bridge in accept the load of both humans and vehicles that cross the bridge and the static equilibrium conditions on the bridge. The construction of a Truss bridge is usually carried out at the place where the bridge will stand. But now the construction of the bridge can be done outside that location, to then be shifted to the actual location. And, that's not only for short bridges, but also for long bridges. But sometimes a condition does not allow conventional bridge construction, while on the other hand the construction of the bridge is something very important. For that we need an innovation, an alternative method so that the construction of the Truss bridge can be carried out. The 100 meter span Australian Truss bridge was assembled above the maintenance bridge at the Batang Arau flood control structure and then shifted downstream to the new bridge location which is 10 meters away. Before the shifting was carried out, rails were prepared as the shifting path and two bridgeheads as the placement of the Truss bridge on the left and right of the Batang Arau river. Currently the Ujung Tanah II Truss bridge has been functioning for 30 years with good maintenance.